(untitled) (Journal of Hama University, 2024)
This research aims to measure and compare levels of technical efficiency in Islamic banks in Syria, This study used Stochastic Frontier Analysis (SFA) to measure and compare levels of the technical efficiency during the period (2016-2020), To achieve this; The method of intermediation approach was followed to determine the banking inputs and outputs. The Frontier 4.1 program was used to measure the technical efficiency of the study sample, which consists of three banks (Al Baraka Bank - Sham Bank - Syria International Islamic Bank) and data were collected through the annual reports of these banks., This research concluded that there are no significant differences between the technical efficiency averages of Islamic banks, and the results indicate that there is a convergence between the efficiency levels of these banks, and this indicates the intensification of competition among them, Al Baraka Bank was ranked first followed by Syrian International Islamic Bank and finally Al Sham Bank.